LA OFERTA NATIVA DE PODCAST EN LA RADIO COMERCIAL ESPAÑOLA: CONTENIDOS, GÉNEROS Y TENDENCIAS - Dra. M.ª de la Peña Mónica PÉREZ-ALAEJOS,Dr. Luis Miguel PEDRERO-ESTEBAN,Dr. Asier LEOZ-AIZPURU (Fonseca, Journal of Communication, 2023)
Close to its first centenary and immersed in a convergence environment, radio begins to design transversal productive models oriented towards the personal consumption of audio according to the main premise in the current eco-system: all contents must be available at all times and for all devices. The podcast acceptance has exponentially grown to create a sound consumption scenario destined to replace to the analogue radio. In this context, traditional operators assume the production of content designed for exclusive online dissemination under segmentation criteria less restricted by the Hertzian market